Career Skills for Surgeons - Panayiotou Charalambous, Charalambos; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book presents various skills to help surgeons improve their day-to-day performance and development including professionalism, communication, situation awareness, decision making, leadership, and technical dexterity. It also offers advice on how to organise a surgical theatre list, improve theatre efficiency, prepare for surgical interviews and participate in surgical research and audit. Furthermore, it emphasises the need to strive for safety in surgery and to learn from things going wrong. The complex world of emotions that surgeons may encounter is also discussed. The guidance presented here may be of value to any aspiring surgeon, whatever their surgical specialty, and wherever they choose to practise. The skills highlighted in this book reflect the author's initial experiences as a surgical trainee, the teachings of his senior trainers, as well as his subsequent involvement in supervising multiple junior surgeons as a Consultant in Trauma and Orthopaedics. Much of the material presented is supported by an extensive literature review. This book complements the previously published book "Career Skills for Doctors" by the same author. .
Part 1. Background -- Part 2. Workplace -- Part 3. Developing Technical skills -- Part 4. Safety in surgery -- Operating theatre checks. .
Keywords: Medicine; Surgery; Medicine & Public Health; Surgery